Os ciclos econômicos eleitorais e o Programa Bolsa-Família - Fabri, David Mendes (2015)
From the dissemination of knowledge about economic voting in the political environment, the increase in real income created by Bolsa Família could create incentives for governments to increase the value of transfers or a broader basis of registered families in order to increase their chances of re-election. The hypothesis tested in this study was that the government influences the costs of the Bolsa Família and increase abnormally in preelection periods. To test this hypothesis, the time series of monthly expenses with the program and the number of beneficiary families have been used since January 2004 to December 2014. For this statistical models were used to identify whether these expenses abnormally increase in periods preceding elections, controlled for other factors that may influence program spending, such as National GDP, Income and Expenses of the National Treasury, Inflation and Unemployment taxes. The results suggest the occurrence of electoral cycles in the presidential election, in which there is an acceleration in the number of families enrolled in the Bolsa Família in the three months prior to the campaign with the increase of program´s costs in the same period, but there is no reduction in the number of families enrolled after the elections and, finally, that there are no effects in the period of the local elections.